Variabel-variabel yang Memengaruhi Perilaku Fertilitas Berisiko Tinggi di Provinsi Nusa Tenggara Timur Tahun 2023 - Sabila, Elsa; Sukim, Sukim (Seminar Nasional Official Statistics, 2025)
One of the factors contributing to the high maternal mortality rate (MMR) is high-risk fertility behavior HRFB). As a province with the highest TFR, NTT Province indicated to have a high prevalence of perilaku fertilitas berisiko tinggi. Although various efforts have been made by the Provincial government to prevent perilaku fertilitas berisiko tinggi, MMR in NTT Province is still high. This indicates that the quality of maternal services in NTT Province is not yet optimal. The purpose of this study was to identify variables that influence the HRFB status of WUS in NTT Province in 2023. The results of the study showed that the variables of women’s education, women’s employment status, use of contraception, ownership of health insurance, and ANC examinations had a significant effect on perilaku fertilitas berisiko tinggi status. In addition, women who have mandatory formal education, are employed, use contraception, have health insurance, and don’t undergo ANC examinations have a greater tendency to have higher-risk HRFB.